2008
DOI: 10.1080/08120090801888594
|View full text |Cite
|
Sign up to set email alerts
|

Paleoproterozoic orogenesis in the southeastern Gawler Craton, South Australia∗

Abstract: Integrated structural, metamorphic and geochronological data demonstrate the existence of a contractional orogen preserved in the ca 1850 Ma Donington Suite batholith along the eastern margin of the Gawler Craton, South Australia. The earliest structures are a pervasive gneissic foliation developed in the Donington Suite and interleaved metasedimentary rocks. This has been overprinted by isoclinal and non-cylindrical folding, and zones of pervasive non-coaxial shear with north-directed transport, suggesting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(25 citation statements)
references
References 54 publications
0
25
0
Order By: Relevance
“…Comparative data for metamorphic monazite is taken from the Mount Woods Domain (Forbes et al, 2011;this study), Corny Point (Reid et al, 2008), and the Fowler Domain (Thomas et al, 2008) (Fig. 1).…”
Section: Metamorphic Monazitementioning
confidence: 99%
“…Comparative data for metamorphic monazite is taken from the Mount Woods Domain (Forbes et al, 2011;this study), Corny Point (Reid et al, 2008), and the Fowler Domain (Thomas et al, 2008) (Fig. 1).…”
Section: Metamorphic Monazitementioning
confidence: 99%
“…Furthermore, the Cornian Orogeny, preserved in the southeastern Gawler Craton (Reid et al 2008) may also form part of the orogenic system responsible for the amalgamation of the Diamantina Craton. The Western Australian Craton remains the same as initially defined (Myers et al 1996) and was formed during the c. 1960 Ma Glenburgh Orogeny (Johnson et al 2013) before it was amalgamated with the rest of the Australian continent.…”
Section: North South and West Australian Cratonsmentioning
confidence: 99%
“…These rocks correlate with the Kalkadoon Batholith in the Mount Isa Terrane, and in the reconstruction of Giles et al (2004) form a continuous magmatic belt. The Donington Suite has an elevated incompatible element signature, 1Nd (1850Ma) values between -2 and -4, and 1Hf (1850Ma) values between 24 and +5.3, suggesting derivation from fractionated mafic crust, with contamination from Archaean crust (Hand et al 2007;Reid et al 2008). Reid et al (2008) suggested that the Donington Suite formed in a continental back-arc region based on the absence of subduction-related geochemical characteristics.…”
Section: Eastern Gawler Cratonmentioning
confidence: 99%
See 2 more Smart Citations